Penguatan Literasi Baca-Tulis Melalui Aktivitas Menulis Karangan Deskripsi Pada Siswa di Madrasah Ibtidaiyah (MI) Ash-Shidiq, Kabupaten Bandung - Devi, Lathifah Sandra; Hayati, Eti; Setiawati (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2024)
Literacy Ability as an Important Early Foundation in Children's Lives. Literacy ability is an important early foundation in children's lives. Children socialize through language, and with their language skills, they are then able to ask questions and construct ideas to communicate to others. The Purpose of Strengthening Literacy. The purpose of strengthening literacy is to provide students with several important goals that have a positive impact on their development, both academically and personally. The Purpose of Students Writing Descriptive Essays The purpose of students writing descriptive essays is to develop their ability to describe or explain an object, place, event, or concept with high detail and clarity. The method of this activity is in the form of a descriptive essay writing activity carried out at the Madrasah Ibtidaiyah (MI) Ash-Shidiqiah School, Bandung Regency. The implementation of student descriptive writing goes through the following stages: Understanding the material of descriptive essays, Types of objects that can be described, Students are then given a theme to be developed into a writing about "The Atmosphere of the School Environment and the Surrounding Environment". The Subjects of This Activity, The students who were given literacy reinforcement in reading and writing were grade V and grade VI students. The Results of This Activity From the activity, it was found that there are internal factors in grades V and VI, namely that it takes a long time to understand the lesson material. Then, external factors are low interest in reading and writing because they are influenced by the culture in the family environment and the availability of facilities and infrastructure, such as the lack of reading books available in the library and publication media in the form of wall magazines. The Role of Teachers Thus, the role of teachers is very important in motivating their interest in reading and writing